A multi-omics spatial framework for host-microbiome dissection within the intestinal tissue microenvironment - Bokai Zhu; Yunhao Bai; Yao Yu Yeo; Xiaowei Lu; Xavier Rovira-Clavé; Han Chen; Jason Yeung; Dingani Nkosi; Jonathan Glickman; Antonio Delgado-Gonzalez; Georg K. Gerber; Mike Angelo; et al. (Nature Communications)
Abstract The intricate interactions between the host immune system and its microbiome constituents undergo dynamic shifts in response to perturbations to the intestinal tissue environment. Our ability to study these events on the systems level is significantly limited by in situ approaches capable of generating simultaneous insights from both host and microbial communities. Here, we introduce Microbiome Cartography (MicroCart), a framework for simultaneous in situ probing of host and microbiome across multiple spatial modalities. We demonstrate MicroCart by investigating gut host and microbiome changes in a murine colitis model, using spatial proteomics, transcriptomics, and glycomics. Our findings reveal a global but systematic transformation in tissue immune responses, encompassing tissue-level remodeling in response to host immune and epithelial cell state perturbations, bacterial population shifts, localized inflammatory responses, and metabolic process alterations during colitis. MicroCart enables a deep investigation of the intricate interplay between the host tissue and its microbiome with spatial multi-omics.